Training at high exercise intensity promotes qualitative adaptations of mitochondrial function in human skeletal muscle - Daussin, Frederic N; Zoll, Joffrey; Ponsot, Elodie; Dufour, Stephane P; Doutreleau, Stephane; Lonsdorfer, Evelyne; Ventura-Clapier, Renee; Mettauer, Bertrand; Piquard, Francois; Geny, Bernard; Richard, Ruddy (Journal of applied physiology (1985), 2008)
1 Physiology and Functional Explorations Department, Centre Hospitalier Régional Universitaire of Strasbourg, Strasbourg; 2 Physiology Department, Faculty of Medicine, University Louis Pasteur, Équipe d'Accueil 3072, Strasbourg; 3 Institut National de la Santé et de la Recherche Médicale, U769, Châtenay-Malabry; 4 University Paris-Sud, Châtenay-Malabry; and 5 Cardiology Department, Civil Hospital, Colmar, France Submitted 24 October 2007 ; accepted in final form 16 February 2008 This study explored mitochondrial capacities to oxidize carbohydrate and fatty acids and functional optimization of mitochondrial respiratory chain complexes in athletes who regularly train at high exercise intensity (ATH, n = 7) compared with sedentary (SED, n = 7). Peak O 2 uptake ( O 2max ) was measured, and muscle biopsies of vastus lateralis were collected. Maximal O 2 uptake of saponin-skinned myofibers was evaluated with several metabolic substrates [glutamate-malate ( GM ), pyruvate ( Pyr ), palmitoyl carnitine ( PC )], and the activity of the mitochondrial respiratory complexes II and IV were assessed using succinate ( s ) and N , N , N ', N '-tetramethyl- p -phenylenediamine dihydrochloride ( TMPD ), respectively. O 2max was higher in ATH than in SED (57.8 ± 2.2 vs. 31.4 ± 1.3 ml·min –1 ·kg –1 , P < 0.001). GM was higher in ATH than in SED (8.6 ± 0.5 vs. 3.3 ± 0.3 µmol O 2 ·min –1 ·g dry wt –1 , P < 0.001). Pyr was higher in ATH than in SED (8.7 ± 1.0 vs. 5.5 ± 0.2 µmol O 2 ·min –1 ·g dry wt –1 , P < 0.05), whereas PC was not significantly different (5.3 ± 0.9 vs. 4.4 ± 0.5 µmol O 2 ·min –1 ·g dry wt –1 ). S was higher in ATH than in SED (11.0 ± 0.6 vs. 6.0 ± 0.3 µmol O 2 ·min –1 ·g dry wt –1 , P < 0.001), as well as TMPD (20.1 ± 1.0 vs. 16.2 ± 3.4 µmol O 2 ·min –1 ·g dry wt –1 , P < 0.05). The ratios S / GM (1.3 ± 0.1 vs. 2.0 ± 0.1, P < 0.001) and TMPD / GM (2.4 ± 1.0 vs. 5.2 ± 1.8, P < 0.01) were lower in ATH than in SED. In conclusion, comparison of ATH vs. SED subjects suggests that regular endurance training at high intensity promotes the enhancement of maximal mitochondrial capacities to oxidize carbohydrate rather than fatty acid and induce specific adaptations of the mitochondrial respiratory chain at the level of complex I. metabolism; exercise training Address for reprint requests and other correspondence: J. Zoll, Service de Physiologie et d'Explorations Fonctionnelles, Hôpital Civil, 1 Place de l'Hôpital, BP 426, F-67091 Strasbourg Cedex, France (e-mail: joffrey.zollatmedecine.u-strasbg.fr )